A Globalization Issue: the Spread of Intolerance Messages on Social Media from the Society's Perspective - Syafitri, Fauziah (Persepsi: Communication Journal, 2025)
This research aims to present a paper that discusses how people's perspectives on globalization issues related to the spread of intolerance messages through social media. The method in this research uses a qualitative method, while the data collection technique uses interviews. Interviews were conducted with 8 respondents who represented the community from among students and education practitioners. The selection of students and education practitioners aims to see the point of view of students as agents of change and education practitioners as part of the community concerned with the world of education, so it is necessary to know the views of both in seeing the phenomenon in this study. The results of this study show that the community, especially from students and educational practitioners, expects social media users to be smarter and wiser in using it, so that it can reduce the number of spread of intolerance messages through social media in Indonesia. The role of the Indonesian government is also very important in providing socialization and education to the community in terms of eradicating messages of intolerance, especially in social media.